Semiotic Community Perspectives on Offerings in Traditional Jathilan Performances in Yogyakarta: A Semiotic Study - Piri, Tirza Benedicta; Avero Pramasheilla, Dinda Assalia; Gustyawan, Tofan; Irianto, Ikhsan Satria (Institut Seni Indonesia Padangpanjang, 2024)
In Javanese terms, Jathilan stands for